PENGARUH MOTIVASI KERJA GURU TERHADAP KINERJA GURU PADA MTSN DI KECAMATAN BONTOTIRO KABUPATEN BULUKUMBA - Andi Agustina; Misykat Malik Ibrahim; Andi Maulana (Idaarah: Jurnal Manajemen Pendidikan, 2020)
This research aimed to analyze the impact of work motivation on teacher’s performance at the MTsN (State Islamic Senior High School) in Bontotiro District Bulukumba Regency. This research is a quantitative study with the ex post facto method. The participants of this research were 67 teachers from MTsN in Bontotiro District. The method of data collection used was questionnaire then the data were analyzed by using regression analysis to test the research hypothesis. The result of this study showed that: 1) the teacher’s work motivation at MTsN in Bontotiro District was in medium category indicating that the teachers work motivation still need to be improved; 2) the teacher’s performance at MTsN in Bontotiro District was in a medium category indicating that the teacher’s performance was not optimal so it still needs to be improved; and 3) the teacher’s work has significant effect on the teacher’s performance at MTsN in Bontotiro District. Thus, the high strength of the teacher’s performance is determined by the strong of weak motivation it possesses.